Demographic and socio-economic determinants of multidimensional financial literacy among young Algerian university students - Yahiaoui, Nour El Houda (Journal of Management and Business Education, 2023)
Financial literacy is crucial for young university students to make sound financial decisions and improve their future well-being. This study examines demographic and socio-economic determinants of multidimensional financial literacy among young Algerian university students. The study employed a cross-sectional survey research design. It broadly adheres to the OECD definition of financial by segregating it into its main dimensions: financial knowledge, behavior, and attitude. Data was gathered from a sample of 368 university students and analyzed using multiple regression analysis. The study found a significant relationship between financial literacy, gender, the field of study, and bank account ownership. Female students are 3.64 times less financially literate than male students. Students majoring in scientific (hard) disciplines are 4.65 times more financially literate than non-scientific (soft) disciplines. Students with no bank account are 4.67 times less financially literate than those who own one. The study found a non-significant relationship between financial literacy and the variables: students’ level of education, the field of specialty, work experience, family income, father’s education level and mother’s education level. What is noticed is that the financial literacy level of economics and major in business students does not differ from those students of other majors.